2013
DOI: 10.1002/stem.1287
|View full text |Cite
|
Sign up to set email alerts
|

Concise Review: Bone Marrow Meets Blastocyst: Lessons from an Unlikely Encounter

Abstract: This article discusses the implications of the recent discovery that rat bone marrow-derived multipotent adult progenitor cells (rMAPCs), a cell type with broad somatic differentiation potential but of uncertain lineage identity, are similar to rat blastocystderived extraembryonic endoderm precursor (rXENP) cells, which appear to represent the committed extraembryonic endoderm precursor of the blastocyst. It was found that under rMAPC culture conditions, rXENP cells can be homogeneously cultured and similar ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Although further studies will be necessary to identify the mode of action and active components involved in MIN6 NV-mediated BM cell differentiation, our in vitro data suggested that the insulin-producing cells that were differentiated in vivo may have been derived from certain lineage-negative BM cells. Because cellular plasticity phenomena are remarkable and are involved in many more cell types than originally thought, , the contributions of different cell populations, including lineage-positive cells, require further investigation. Nonetheless, the usage of naïve whole BM cells has additional benefits over the use of cultured (pluripotent) cells, which have tumorigenic potential. , …”
Section: Resultsmentioning
confidence: 99%
“…Although further studies will be necessary to identify the mode of action and active components involved in MIN6 NV-mediated BM cell differentiation, our in vitro data suggested that the insulin-producing cells that were differentiated in vivo may have been derived from certain lineage-negative BM cells. Because cellular plasticity phenomena are remarkable and are involved in many more cell types than originally thought, , the contributions of different cell populations, including lineage-positive cells, require further investigation. Nonetheless, the usage of naïve whole BM cells has additional benefits over the use of cultured (pluripotent) cells, which have tumorigenic potential. , …”
Section: Resultsmentioning
confidence: 99%
“…These data suggest that murine bone marrow cells do not transdifferentiate into cell types of diverse lineages, but inherently contain more diverse and primitive stem cell populations that could develop into conventional three germ layer components depending on their in vitro or in vivo microenvironment. 30 Our protocol for differentiation of functioning hepatocytes from bone marrow cells is unusually simple and efficient. Moreover, similar to pluripotent stem cell differentiation protocols, we successfully reiterated the various normal-like sequential developmental stages, which guarantee more physiologically relevant cells.…”
Section: Discussionmentioning
confidence: 99%
“…It is also interesting to point out here that OCT-4 is one of the sensitive markers increasingly being used for diagnosis of carcinoma in situ in germ cell tumors [25,26]. Several groups have suggested that [27,28], these VSELs may be the similar to the MAPCs described by Verfaillie's group [29]. Many groups have reported successful derivation of ES-like colonies from testicular tissue culture in mice [30] as well as in humans [31,32] and proposed the origin of the colonies to be dedifferentiation of SSCs.…”
Section: Introductionmentioning
confidence: 62%